Shadow banking: Policy challenges for central banks - Thorvald Grung Moe (Levy Economics Institute of Bard College, 2014)
Central banks responded with exceptional liquidity support during the financial crisis to prevent a systemic meltdown. They broadened their tool kit and extended liquidity support to nonbanks and key financial markets. Many want central banks to embrace this expanded role as "market maker of last resort" going forward. This would provide a liquidity backstop for systemically important markets and the shadow banking system that is deeply integrated with these markets. But how much liquidity support can central banks provide to the shadow banking system without risking their balance sheets? I discuss the expanding role of the shadow banking sector and the key drivers behind its growing importance. There are close parallels between the growth of shadow banking before the recent financial crisis and earlier financial crises, with rapid growth in near monies as a common feature. This ebb and flow of shadow-banking-type liabilities are indeed an ingrained part of our advanced financial system. We need to reflect and consider whether official sector liquidity should be mobilized to stem a future breakdown in private shadow banking markets. Central banks should be especially concerned about providing liquidity support to financial markets without any form of structural reform. It would indeed be ironic if central banks were to declare victory in the fight against too-big-to-fail institutions, just to end up bankrolling too-big-to-fail financial markets.
Keywords: E44; E52; E58; G28; 330; Financial Regulation; Financial Stability; Monetary Policy; Central Bank Policy